Reactive metabolite activation by CYP2C19-mediated rhein hepatotoxicity. (19th November 2014) - He, Li-Na; Yang, Ai-Hong; Cui, Tian-Yi; Zhai, Yi-Ran; Zhang, Fang-Liang; Chen, Jun-Xiu; Jin, Chun-Huan; Fan, Yao-Wen; Wu, Zi-Jun; Wang, Li-Li; He, Xin
Abstract: 1. Rhein, an active ingredient in the root of rhubarb, is used for its beneficial effects in a variety of clinical applications including the treatment of osteoarthritis and diabetic nephropathy. However, its hepatotoxicity has been reported in recent years. Rhein belongs to the conjugate structure which could be activated to reactive metabolites (RMs) inducing side-effects. This study is to explore the relationship between RMs and hepatotoxicity. 2. Based on the early detection of RMs, we have established a series of key technologies to research rhein hepatotoxicity mechanism: IC50 shift experiments and reduced glutathione (GSH) trapping experiment are adopted to identify RMs. The model of low activity of CYP450 enzymes (CYPs) in primary rat hepatocyte is constructed to analyze the relationship between the primary metabolic enzyme and hepatotoxicity of rhein better. 3. The IC50 shift value for CYP2C19 is 1.989, it suggests that CYP2C19 could activate rhein to RM. The structure of RM is epoxide intermediate. Besides, it is found that CYP2C19 is a primary metabolic enzyme for rhein. In the cytotoxicity assay, it is reported that rhein could cause mitochondrial dysfunction. Furthermore, mitochondrial membrane potential (Δ ψ m ) and AST levels could be restored by adding inhibitor of CYP2C19 together with rhein, which further shows that CYP2C19 could mediate the hepatotoxicity of rhein. 4. We put forward the possible mechanism that reactive metabolite activation by CYP2C19 mediated rhein hepatotoxicity, it provides important information on predicting in vivo drug-induced liver injury (DILI).